A remarkable case of basis set dependence: the false convergence patterns of the methyl anion*. (18th June 2019) - Bowman, Michael C.; Zhang, Boyi; James Morgan, W.; Schaefer, Henry F.
ABSTRACT: The gas phase methyl anion, CH 3 −, has been difficult to study experimentally, and the extreme basis set dependence of its molecular properties has presented a comparable challenge to theoreticians. Reliable predictions for the electronic structure of CH 3 − require the use of basis sets capable of describing both the diffuse and valence characteristics of the system. The present study examines the basis set dependence of the equilibrium geometry and harmonic vibrational frequencies of CH 3 − . Both Hartree–Fock and CCSD(T) levels of theories are used with cc-pV X Z ( X = D, T, Q, 5, 6) basis sets with up to triple augmentation to describe the diffuse nature of the electron distribution. We find that non-augmented basis sets systematically yield vibrational frequencies that are too high for the umbrella mode and too low for the C–H symmetric and antisymmetric stretch even when extrapolated to the complete basis set limit, displaying false convergence patterns. The inclusion of one set of augmented functions significantly improves the convergence of these properties, but again yields false convergence patterns. Only with the doubly augmented basis set do we approach the basis set limit for the CH 3 − vibrational frequencies. GRAPHICAL ABSTRACT: